The phylogenetic position of the world's smallest passerine, the Pygmy Bushtit Psaltria exilis. (26th April 2016) - Johansson, Ulf S.; Ericson, Per G. P.; Fjeldså, Jon; Irestedt, Martin
Abstract : The Pygmy Bushtit is confined to the montane forests of Java. It is the world's smallest passerine and morphologically resembles a small, drab long‐tailed tit or bushtit (Aegithalidae). In its behaviour the Pygmy Bushtit show similarities with the members of the Aegithalidae, but owing to its small size and isolated geographical distribution relative to the other members of the Aegithalidae, it has always been placed in a monotypic genus within the family. The affinities of the Pygmy Bushtit have never been tested in a phylogenetic context and the species has to date not been included in any molecular studies. In this study we use sequence data from four different genetic markers to place it in the passerine phylogenetic tree. Our results confirm the inclusion of the Pygmy Bushtit in the Aegithalidae, but rather than being an isolated lineage, our results strongly suggest that it is nested in the Aegithalos clade, and most closely related to the Black‐throated Bushtit Aegithalos concinnus . The range of the Black‐throated Bushtit extends south into subtropical Indochina, with an isolated subspecies occurring in southern Vietnam. The Black‐throated Bushtit contains several morphologically and genetically distinct lineages, which could represent distinct species, but the phylogenetic relationships within this complex are poorly resolved and partly in conflict with current taxonomic treatment based on morphology.